Autonomous nervous system responses to environmental‐level exposure to 5G's first deployed band (3.5 GHz) in healthy human volunteers - Layla Jamal; Lisa Michelant; Stéphane Delanaud; Laurent Hugueville; Paul Mazet; Philippe Lévêque; Tamara Baz; Véronique Bach; Brahim Selmaoui (Experimental Physiology)
Abstract Following the global progressive deployment of 5G networks, considerable attention has focused on assessing their potential impact on human health. This study aims to investigate autonomous nervous system changes by exploring skin temperature and electrodermal activity (EDA) among 44 healthy young individuals of both sexes during and after exposure to 3.5 GHz antenna‐emitted signals, with an electrical field intensity ranging from 1 to 2 V/m. The study employed a randomized, cross‐over design with triple‐blinding, encompassing both ‘real’ and ‘sham’ exposure sessions, separated by a maximum interval of 1 week. Each session comprised baseline, exposure and postexposure phases, resulting in the acquisition of seven runs. Each run initiated with a 150 s segment of EDA recordings stimulated by 10 repeated beeps. Subsequently, the collected data underwent continuous decomposition analysis, generating specific indicators assessed alongside standard metrics such as trough‐to‐peak measurements, global skin conductance and maximum positive peak deflection. Additionally, non‐invasive, real‐time skin temperature measurements were conducted to evaluate specific anatomical points (hand, head and neck). The study suggests that exposure to 3.5 GHz signals may potentially affect head and neck temperature, indicating a slight increase in this parameter. Furthermore, there was a minimal modulation of certain electrodermal metrics after the exposure, suggesting a potentially faster physiological response to auditory stimulation. However, while the results are significant, they remain within the normal physiological range and could be a consequence of an uncontrolled variable. Given the preliminary nature of this pilot study, further research is needed to confirm the effects of 5G exposure.